Virgin Coconut Oil (VCO) Enriched with Zn as Immunostimulator for Vaginal Candidiasis Patient - HERY WINARSI; HERNAYANTI HERNAYANTI; AGUS PURWANTO (Bogor Agricultural University, Indonesia, 2008)
Disturbance on the immune system and deficiency of Zn is two factors which often trigger vaginal candidiasis patient. The aim of the research was to study the effect of virgin coconut oil (VCO) enriched with Zn to the amount of neutrophil and lymphocyte subset cells, and the level of IL-2 and IgG in vaginal candidiasis patient. Thirty women were grouped into three (ten women in each group): A, B and C, and intervened for two months. Women in A group were intervened with two tablespoon/day; those in B group were intervened with one tablespoon/day; while those in C group served as control (placebo). Blood was sampled at baseline time, one and two months after intervention. Hematological test by Micros-OT was done on a part of blood, and the plasma was used for IL-2 and IgG level tests using ELISA. The virgin coconut oil enriched with Zn maintained the number of neutrophil and NK cells, but increased Tc cells from 521 to 649 cells/mm3, increased Th cells from 1.090 to 1.380 cells/mm3. The enriched VCO also increase level of IL-2 from 0.25313 to 0.27337 pg/ml, while the IgG level changed from equivocal to negative. The recommended dosage was one tablespoon each day. Key words: IL-2, IgG, neutrophil, NK, Th and Tc-cells, VCO, Zn